Shooting the Family Transnational Media and Intercultural Values - Pisters, Patricia; Staat, Wim (Amsterdam University Press, 2005)
Do contemporary movements of migration and the ever-increasing abundance of audiovisual media correspond to - or even cause - shifts in the defenition of both the bourgeois nuclear family and the tribal extended family? In Shooting the Family, twelve authors investigate the transfigured role of the family in a transnational world in which intercultural values are negotiated through mass media like film and television, as well as through particularistic media like home movies and videos. "Shooting the Family" has a double meaning. On the one hand, this book claims that the family is under pressure from the forces of globalization and migration; it is the family that risks being shot to pieces. On the other hand, family matters of all kinds, including family values, are increasingly being constructed and refigured in a mediated form. The audiovisual family has become an important medium for intercultural affairs - this is a family that is being re-established as a place of security and comfort in times of upheaval; it is the family shot by cameras that register and simultaneously create new family values. This title is available in the OAPEN Library - http://www.oapen.org.